2000
DOI: 10.1046/j.1469-7580.2000.19640501.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the basal ganglia: new perspectives through a comparative approach

Abstract: The basal ganglia (BG) have received much attention during the last 3 decades mainly because of their clinical relevance. Our understanding of their structure, organisation and function in terms of chemoarchitecture, compartmentalisation, connections and receptor localisation has increased equally. Most of the research has been focused on the mammalian BG, but a considerable number of studies have been carried out in nonmammalian vertebrates, in particular reptiles and birds. The BG of the latter 2 cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 88 publications
(62 reference statements)
6
119
1
Order By: Relevance
“…In contrast, in rats, one remarkable aspect of our findings is that the vast majority of the DA neurons that project to the striatum also project to the MLR, implying a simultaneous ascending and descending modulation of the entire locomotor command circuitry from cortex to brainstem. These DA neurons are mostly located in the SNc with a few in the RRF, two structures that are classically considered as mesencephalic but that also span in the diencephalon (16,19,20). In lampreys, the terminology "mesodiencephalic DA neurons" does not apply, given that the DA neurons are all located in the diencephalon (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in rats, one remarkable aspect of our findings is that the vast majority of the DA neurons that project to the striatum also project to the MLR, implying a simultaneous ascending and descending modulation of the entire locomotor command circuitry from cortex to brainstem. These DA neurons are mostly located in the SNc with a few in the RRF, two structures that are classically considered as mesencephalic but that also span in the diencephalon (16,19,20). In lampreys, the terminology "mesodiencephalic DA neurons" does not apply, given that the DA neurons are all located in the diencephalon (40).…”
Section: Discussionmentioning
confidence: 99%
“…In lampreys and teleosts, those neurons are located only in the diencephalon (posterior tuberculum), but in tetrapods and cartilaginous fishes (14) they are located in both the diencephalon and the mesencephalon. An increasing number of authors seem to agree with the hypothesis that at least some of the mesodiencephalic DA neurons located in the diencephalon are homologous in all vertebrates, and thus, homologous to at least a portion of the mammalian substantia nigra pars compacta (SNc)/ ventral tegmental area (VTA) (13,(15)(16)(17)(18)(19); for review, see ref. 20).…”
mentioning
confidence: 87%
“…The dorsal portion consists of the STR (caudate putamen in most mammals) and the dorsal pallidum, while the ventral portion consists of the NAcc and VP. It was previously thought that the basal ganglia were only present in amniotes (MacLean, 1990), but many studies in the past decade have shown that amphibians clearly possess the basal ganglia regions (Smeets et al, 2000) and teleosts likely do so as well (Wullimann and Mueller, 2004). In the following, we focus mainly on neurochemical, developmental, and hodological studies to support homologies across vertebrates, although we discuss lesion or stimulation studies where available in order to comment on whether these homologous structures are functionally similar.…”
Section: Neuroanatomy Of Social Behaviormentioning
confidence: 99%
“…Although both amphibians and teleosts lack a midbrain dopaminergic cell group (Smeets et al, 2000), multiple lines of evidence point to the posterior tuberculum, located in the ventral diencephalon, as the putative anamniote VTA homolog. Wullimann (2001, 2002) found that the posterior tuberculum is the teleost dopaminergic system ascending to the striatum, similar to mammals (Fallon and Moore, 1978), and suggested that this region in teleosts might be functionally similar and possibly homologous to the mammalian VTA/ substantia nigra pars compacta.…”
Section: Amphibians and Teleostsmentioning
confidence: 99%
See 1 more Smart Citation